Naturally Occurring Microbiota Associated with Mosquito Breeding Habitats and Potential Parasitic Species against Mosquito Larvae: A Study from Gampaha District, Sri Lanka. (28th April 2020) - Ranasinghe, H. A. K.; Amarasinghe, L. D.
Abstract : A mosquito species has its own favourable requirements of abiotic and biotic characteristics including microbiota, in a breeding habitat. Some of the microbiota may cause parasitic or pathogenic effects to mosquito larvae such as species of viruses, parasitic bacteria, fungi, protists, entomopathogenic nematodes, and filamentous fungi. In Sri Lanka, there is a scarcity of information on microbiota associated with mosquito breeding habitats and their effect on mosquito larvae. Hence, the present study was conducted to determine microbiota species/taxa associated with a variety of mosquito breeding habitats in selected areas of the Gampaha District in Sri Lanka and the relationship, if any, the microbiota has with mosquito larva survival and breeding. Forty-five microbiota species belonging to 11 phyla were found from different mosquito breeding habitats with the highest percentage belonging to phylum Euglenozoa (27.89%). Species that belonged to the phylum Amoebozoa (1.22%) and Sarcodina (1.17%) had the lowest abundance, and each of its species richness was recorded as one. Philodina citrina followed by Monostyla bulla comprised 30.8% and 16.59%, respectively, of the total rotifer population. From the total microbiota, 25-50% existed as accidental while less than 25% rare, in the habitat type according to their abundance. Paddy fields had the highest species richness (17), evenness (23.52), Shannon-Weiner (66.64), and beta diversity (0.65) over 50% indicating high heterogeneity in microbiota composition among the habitats. Ciliated protists, namely, Vorticella microstoma, Zoothamnium spp., and Chilodinella sp., were identified as naturally occurring microbiota associated with Culex mosquito larvae that inhabited in paddy fields and associated irrigation canals. Only Vorticella microstoma caused a significant lethal effect on mosquito larvae . This study revealed that species of Cx. gelidus, Cx. pseudovishnui, Cx. tritaeniorhynchus, Cx. quinquefasciatus, and Cx. whitmorei served as hosts for V. microstoma where infectivity rate in Cx. tritaeniorhynchus reached 73.22. Chilodinella sp. selectively served as endoparasitic to Cx. gelidus larvae causing only 4.58% mortality, and invasive cysts of the pathogen were observed in the subcuticular layer of the host body. Even though Zoothamnium spp. were found on Cx. tritaeniorhynchus larvae, there was no lethal effect due to the attachment of the parasitic agent. The potential of these microbiotas in integrated vector controlling approaches in future perspectives is recommended.